Effect of Combination Antiretroviral Therapy on HIV-1-specific Antibody-Dependent Cellular Cytotoxicity Responses in Subtype B- and Subtype C-Infected Cohorts. (1st July 2017) - Madhavi, Vijaya; Kulkarni, Archana; Shete, Ashwini; Lee, Wen S.; Mclean, Milla R.; Kristensen, Anne B.; Ghate, Manisha; Wines, Bruce D.; Hogarth, Phillip M.; Parsons, Matthew S.; Kelleher, Anthony; Cooper, David A.; et al.
Abstract : Background: There is growing interest in immune therapies to clear the latent HIV-1 after combination antiretroviral therapy (cART). There is limited information on the effect of cART on antibody-dependent cellular cytotoxicity (ADCC), and no studies have directly compared ADCC in HIV-1 subtype B- and subtype C-infected subjects. The effect of improving immunocompetence on ADCC to influenza also remains unexplored. Methods: The effect of cART on HIV-1- and influenza-specific ADCC was analyzed in 2 cohorts (39 subtype B- and 47 subtype C-infected subjects) before and after 2 years of cART. ADCC analyses included an enzyme-linked immunosorbent assay–based dimeric recombinant soluble (rs) FcγRIIIa-binding assay, antibody-dependent natural killer cell activation assay, and ADCC-mediated killing assays. Results: HIV-1 subtype B and C Env-specific antibody binding to dimeric rsFcγRIIIa were reduced in subtypes B- and C-infected cohorts after 2 years of cART (both P < 0.05). Reduced ADCC-mediated killing of target cells expressing subtype B Env in the subtype B-infected cohort ( P = 0.003) was observed after 96 weeks of cART, but not of subtype C Env in the subtype C-infected cohort. A greater reduction in ADCC was detected in subjects with baseline CD4 counts >300 cells/μL ( P < 0.05). The resolving immunodeficiency after 96 weeks of cART resulted in improved HA-specific ADCC to 6 strains of influenza (all P < 0.01). Conclusions: cART results in HIV-1 antigen loss and reductions in HIV-1 Env-specific antibodies with Fc functionality in both subtype B- and C-infected subjects, particularly in immunocompetent subjects. Simultaneously, cART improves ADCC to diverse strains of influenza, suggesting reduction in influenza disease after cART. Abstract : Supplemental Digital Content is Available in the Text.